Age-related cognitive changes and distributed leadership. Issue 3 (13th April 2015) - Rose, Dennis Michael; Gordon, Raymond
Abstract : Purpose: – The purpose of this paper is to examine the evidence for age-related changes in cognition and the implications for leadership styles. In particular, a case is argued for distributed forms of leadership that encourage contribution across the age spectrum and hierarchical levels. Design/methodology/approach: – This paper takes a conceptual approach, combining the psychology and management literatures in arguing the case for newer leadership forms, appropriate to an ageing workforce. Findings: – Three principal components of intelligence (fluid, and crystallised intelligence and working memory) are considered and it is argued that high levels of fluid intelligence, generally higher in younger employees, should be accessed while being balanced by crystallised intelligence (experience). Distributed leadership has been mainly applied in educational settings. This paper argues for distributed leadership to maximise creativity and innovation. Practical implications: – Leadership forms that maximise creative input from staff across all age levels are likely to contribute to firm innovation and sustainability. Additionally, job satisfaction and turnover among junior staff may be positively influenced through opportunities for greater participation. Social implications: – The elements discussed in this paper address important leadership issues for managing a multigenerational workforce. Originality/value: – Distributed leadership has been discussed in educational and health literatures for some time; however it is only recently that this approach to leadership has appeared in mainstream management literature. The discussion of age-related changes and distributed leadership introduces and important topic for further research in newer forms of leadership.